2020
DOI: 10.1007/s12350-018-1272-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced photon count levels and choice of normal data on semi-automated image assessment in cardiac SPECT

Abstract: Significant bias results from count level of normal data relative to actual patient data. Compared to standard LEHR, IQ-SPECT should allow for significant dose reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The latest generations of dedicated cardiac SPECT cameras and advanced iterative reconstruction software methods (7)(8)(9)(10)(11) have enabled meaningful reductions in imaging time and radiopharmaceutical doses (12)(13)(14)(15)(16). However, if the reconstruction parameters are not adjusted for increased noise in the reduced-dose/time images, it may be necessary to use normal databases that are ''countmatched'' to avoid bias induced by the noise mismatch between the normal database and the reduced-dose/time images (15)(16)(17). Another factor that affects the normal perfusion distribution patterns is camera technology; Figure 3 illustrates examples of the mean normal perfusion polar map differences in regional relative perfusion between SPECT and PET normal patterns, standard SPECT versus cadmium-zinc-telluride imaging, and attenuation correction versus studies not corrected for attenuation.…”
Section: Established Clinical Applications Database Relative Myocardimentioning
confidence: 99%
“…The latest generations of dedicated cardiac SPECT cameras and advanced iterative reconstruction software methods (7)(8)(9)(10)(11) have enabled meaningful reductions in imaging time and radiopharmaceutical doses (12)(13)(14)(15)(16). However, if the reconstruction parameters are not adjusted for increased noise in the reduced-dose/time images, it may be necessary to use normal databases that are ''countmatched'' to avoid bias induced by the noise mismatch between the normal database and the reduced-dose/time images (15)(16)(17). Another factor that affects the normal perfusion distribution patterns is camera technology; Figure 3 illustrates examples of the mean normal perfusion polar map differences in regional relative perfusion between SPECT and PET normal patterns, standard SPECT versus cadmium-zinc-telluride imaging, and attenuation correction versus studies not corrected for attenuation.…”
Section: Established Clinical Applications Database Relative Myocardimentioning
confidence: 99%
“…While the diagnostic and prognostic advantages of dedicated cardiac SPECT systems are already well reported [ 1 , 2 , 16 18 , 23 , 26 ], the clinical use of general-purpose SPECT systems equipped with cardiac specific collimators is still very relevant [ 2 , 15 , 16 , 27 ]. In case of the heart-focused collimators the imaging performance [ 11 , 13 , 28 , 29 ] along with the accurate clinical use [ 12 , 30 – 34 ] has been already thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have shown that when a cardiofocal collimator is used instead of a LEHR collimator, the injected activity is reduced by up to 67% [12] or a factor of four [13]. However, neither study proposed how to tailor the injected activity to the individual patient, nor did they determine the degree of patient size-related gamma-ray signal attenuation.…”
Section: Introductionmentioning
confidence: 99%